Luminous moments the contemporary sacred - McCredden, Lyn, 1953- (Hindmarsh, S. Aust. : ATF Press, 2010)
Luminous Moments is an idea, a way of seeing, an imaginative practice of openness to the everyday and the random. In the early twenty-first century, human beings seek new ways of constructing and comprehending ultimate meanings. For many, the revival of evolutionary thinking, along with the centenary of Darwin, is creating a new faith. Long live the prophets Richard Dawkins and Christopher Hitchens! For others, the earth in all its beauty and its present agonies is where they seek to understand their existence. The institutions of church, mosque, temple or shrine still hold out the promise of
Chapter One; Popular Cultures/Sacredness; Chapter Two; Postmodern Rituals:; Contemporary Australia Responds to Bali; Chapter Three; The Impossible Infinite:; Les Murray, Poetry, and the Sacred; Chapter Four; Tim Winton: Dirt Music and Dreams of Renewal; Chapter Five; Forms of Memory in Post-Colonial Australia; Chapter Six; Sacred Exchange: Peter Carey's Oscar and Lucinda; Chapter Seven; Contemporary Sacredness: The City Poetry of; Vincent Buckley and Sam Wagan Watson; Chapter Eight; 'Untranscended Life Itself':; The Poetry of Pam Brown; Chapter Nine; The Carnal Theologies of Nick Cave
Includes index.
Keywords: Religion and culture; Religion in literature; Religion and literature; Australian literature -- History and criticism; Sacred books; Sacred music; Spirituality; RELIGION / Sexuality & Gender Studies; Electronic books